Development and validation of the illness perceptions questionnaire for youth anxiety and depression (IPQ-Anxiety and IPQ-Depression) - Bear, HA; Moon, Z; Wasil, A; Ahuvia, I; Edbrooke-Childs, J; Wolpert, M (Taylor & Francis, 2023)
Background: The Revised Illness Perceptions Questionnaire (IPQ-R) is a well-established measure for measuring illness representations with sound psychometric properties. However, one limitation is that it provides a generic measure of illness representations and lacks specificity to individual health conditions, making it difficult to capture the nuances of illness beliefs for different populations.